P05.05.B A new IDH-wildtype glioma subtype characterized by highly diffuse growth pattern, distinct epigenetic profile and relatively favorable prognosis. (5th September 2022) - Münch, A; Teichmann, D; Kuzman, P; Spille, D; Perez, E; May, S; Mueller, W; Kombos, T; Nazari-Dehkordi, S; Onken, J; Vajkoczy, P; Ntoulias, G; et al.
Abstract: Background: DNA methylation profiling has emerges as a powerful approach to CNS tumor classification and the discovery of novel, molecularly distinct entities. With the release of the 12.5 version of the Heidelberg Brain Tumor Classifier, some unclassifiable cases can be assigned to novel methylation classes. We retrospectively reviewed our databases and identified 16 previously unclassifiable cases, all of which belong to the provisional methylation class "adult-type diffuse high-grade glioma, IDH-wildtype, subtype F (HGG_F)". Material and Methods: We clinically, radiologically and morphologically characterized 16 HGG_F cases and compared them to 347 glioblastomas. We additionally analyzed copy-number alterations and performed DNA exome sequencing. Results: Median age at diagnosis of the 12 males and 4 females was 65 years. Upon initial diagnostic workup, specimens were classified as CNS tissue with reactive changes (n=3) or suspicious for the infiltration zone of a diffuse glioma (n = 13). None of the cases demonstrated endothelial proliferation or necrosis and 10/16 tumors had flat copy number profiles. Radiological characteristics were reminiscent of gliomatosis cerebri in eight cases and 9/9 cases had normal FET-PET scans. Whole-exome sequencing revealed genetic alterations frequently found in IDH-wildtype glioblastomas, including TERT promoter mutations in 11/14 (78.6%) and PIK3 mutations (10/14, 71.4%). Outcome was significantly better compared to TCGA IDH-wildtype glioblastomas with a median progression-free survival of 58 months and overall survival of 73 months (both p<0.001). Conclusion: We provide evidence that TERT promoter mutations in diffusely infiltrating gliomas without further morphological or molecular signs of high-grade glioma should be interpreted in the context of the clinico-radiological presentation as well as epigenetic prolife and may not be suitable as standalone diagnostic marker for glioblastoma, IDH wildtype.